Therapeutic delivery of calcitonin to inhibit external inflammatory root resorption. II. Influence of calcitonin binding to root mineral - Wiebkin, O W; Cardaci, S C; Heithersay, G S; Pierce, A M (Endodontics & dental traumatology, 1996)
Experimentally-induced external inflammatory tooth-root resorption can be inhibited by therapeutic doses of calcitonin. Such doses can be delivered by an intrinsically slow diffusion pathway, from a reservoir in endodontically-debrided root canals, via the dentinal tubules. While the kinetics of this journey have been followed in an earlier report, the binding characteristics of calcitonin to the tooth mineral, which will be responsible, in part, for these kinetics, have not been reported before. The current study examines the binding potential of calcitonin to root mineral and addresses the potential role of non-specific binding proteins. A modified Scatchard plot indicated that a simple non-reactive type of ligand binding exists between calcitonin and root mineral, represented by a small number of identical binding sites. This interaction is both strong and reversible. Furthermore, it appears to be time-dependent with more time being required for the residual ligands to interact with the diminishing numbers of free calcitonin-binding sites. While preloaded [125I]-calcitonin could be incompletely (75-91%) displaced from dental-root material by non-radioactive calcitonin, its release was slow over 23 h. Calcitonin was four times as effective as bovine-serum albumin in competing for common "calcitonin binding sites" on macerated dental-root material. Thus, even in the presence of extraneous protein, calcitonin will bind tightly but reversibly to tooth-root material, making it a good candidate for therapeutically protracted delivery to external root surfaces from root canals.